1996
DOI: 10.1038/nm0196-35
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tissue factor induced by oxygen free radicals on coronary flow during reperfusion

Abstract: Tissue factor is a transmembrane protein that activates the extrinsic coagulation pathway by binding factor VII. Endothelial cells, being in contact with circulating blood, do not normally express tissue factor. Here we provide evidence that oxygen free radicals induce tissue factor messenger RNA transcription and expression of tissue factor procoagulant activity in endothelial cells in culture. Isolated, perfused rabbit hearts exposed to exogenous oxygen free radicals also showed a marked increase in tissue f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
2
4

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(123 citation statements)
references
References 32 publications
5
112
2
4
Order By: Relevance
“…One of the first indications for a nonhemostatic function of TF was its characterization as an immediate early gene that can be induced during cell division 16 and in response to pathophysiologically relevant stimuli, such as cytokines, 17 growth factors, 18 oxidized LDL, 19 and oxygen free radicals. 20 An exciting recent development in TF biology was the demonstration that this protein, a member of the cytokine receptor superfamily, can function as a true signaling receptor. Indeed, signaling via TF has now been documented in many different cell types, including keratinocytes, bladder carcinoma cells, COS-1, and BHK cells.…”
Section: Discussionmentioning
confidence: 99%
“…One of the first indications for a nonhemostatic function of TF was its characterization as an immediate early gene that can be induced during cell division 16 and in response to pathophysiologically relevant stimuli, such as cytokines, 17 growth factors, 18 oxidized LDL, 19 and oxygen free radicals. 20 An exciting recent development in TF biology was the demonstration that this protein, a member of the cytokine receptor superfamily, can function as a true signaling receptor. Indeed, signaling via TF has now been documented in many different cell types, including keratinocytes, bladder carcinoma cells, COS-1, and BHK cells.…”
Section: Discussionmentioning
confidence: 99%
“…antibodies, to degranulation and the production of reactive oxygen species, resulting in endothelial cytotoxicity (2,(6)(7)(8)(9). Interestingly, Golino et a1 have shown that reactive oxygen species produced by neutrophils induce TF expression on endothelial cells (43). In addition, we and others have shown that reactive oxygen species, anti-PR3, IL-1, and TNFa (alone or in combination) can increase the capacity of the endothelium to bind neutrophils (20)(21)(22)25,28,44).…”
Section: Discussionmentioning
confidence: 99%
“…Accelerated activation of the coagulation system may lead to pathological conditions, such as stroke 23 and coronary artery disease. 24 On the other hand, certain factor VII genotypes associated with lower plasma factor VII levels (and thus lower prothrombinase activity) are thought to protect against myocardial infarction. 25 Platelets express this procoagulant activity in response to collagens or CVX in a dose-dependent manner, as reported by Alberio et al 11 and confirmed by our results in the present study.…”
Section: Furihata Et Almentioning
confidence: 99%